How the mind explains behavior : folk explanations, meaning, and social interaction - Malle, Bertram F. (Bradford Bks., 2004)
In this provocative monograph, Bertram Malle describes behavior explanations as having a dual nature -- as being both cognitive and social acts -- and proposes a comprehensive theoretical model that integrates the two aspects. When people try to understand puzzling human behavior, they construct behavior explanations, which are a fundamental tool of social cognition. But, Malle argues, behavior explanations exist not only in the mind; they are also overt verbal actions used for social purposes. When people explain their own behavior or the behavior of others, they are using the explanation to manage a social interaction -- by offering clarification, trying to save face, or casting blame. Malle's account makes clear why these two aspects of behavior explanation exist and why they are closely linked; along the way, he illustrates the astonishingly sophisticated and subtle patterns of folk behavior explanations. Malle begins by reviewing traditional attribution theories and their simplified portrayal of behavior explanation. A more realistic portrayal, he argues, must be grounded in the nature, function, and origins of the folk theory of mind -- the conceptual framework underlying people's grasp of human behavior and its connection to the mind. Malle then presents a theory of behavior explanations, focusing first on their conceptual structure and then on their psychological construction. He applies this folk-conceptual theory to a number of questions, including the communicative functions of behavior explanations, and the differences in explanations given for self and others as well as for individuals and groups. Finally, he highlights the strengths of the folk-conceptual theory of explanation over traditional attribution theory and points to future research applications.